(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
We propose to analyze the textual configuration of two contemporary novels. On the one hand, Catálogo de las formas (2014) by the argenmex writer Nicolás Cabral and, on the other hand, Conjunto vacío (2017) by the Mexican visual artist who writes Verónica Gerber Bicecci. We read them in series because both authors are encompassed within a second generation of hijxs of the Argentine exile in Mexico. We will dwell on the observation of a writing that exceeds the text and goes beyond conventional literary forms. In addition, reading also plays a central role, since together they shape personal memories in order to understand the events of the past. Art crosses the modes to which we refer, in this case heterogeneous narratives that involve the visual, the historical and even a limited linear writing that exposes a different narrative memory.